Large mismatch profile predicts rapidly progressing brain edema in acute anterior circulation large vessel occlusion patients undergoing endovascular thrombectomy - Shao, Yanqi; Chen, Xinyi; Wang, Huiyuan; Shang, Yafei; Xu, Jie; Zhang, Jinshi; Wang, Peng; Geng, Yu (Frontiers in Neurology, 2023)
Background: Brain edema is a serious complication in patients with large vessel occlusion (LVO), which can reduce the benefit of endovascular therapy (EVT). This study is to investigate the association of perfusion profile at baseline CT-perfusion with rapidly progressing brain edema（RPBE）after EVT in acute anterior LVO patients. Methods: We retrospectively reviewed consecutively collected data of 149 anterior LVO patients who received EVT in our center. Brain edema was measured by swelling score (0-6 score) and RPBE was defined as the swelling score increased more than 2-scores within 24-hours after EVT. We evaluated the affect of RPBE on poor outcomes in hospital (NIHSS score and mRS score at discharge, occurrence of hemorrhagic transformation and mortality rate in hospital) using Mann–Whitney U-test and Chi-Square-test. Multivariate logistic regression model was performed to assess the relationship between perfusion imaging parameters and the occurence of RPBE. Results: Overall, 39 patients (26.2%) occurred RPBE after EVT. RPBE was associated with higher NIHSS score (Z=3.52, 95%CI 2.0-12.0, P<0.001) and higher mRS score (Z=3.67, 95%CI 0.0-1.0, P<0.001) at discharge as well as more frequent occurrence of hemorrhagic transformation (2=22.17, 95%CI 0.29-0.59, P<0.001) and higher mortality rate in hospital (2=9.54, 95%CI 0.06-0.36, P=0.002). Univariate analysis showed that intravenous thrombolysis, baseline ischemic core volume, baseline mismatch ratio were correlated with RPBE (all P<0.05). After divided mismatch ratio into quartiles and performed Chi-Square-test between quartiles, we found that the occurrence of RPBE in Q4 (mismatch ratio >11.3) was significantly lower than that of Q1 (mismatch ratio≤3.0)（P<0.05）. Multivariate logistic regression analysis revealed that compared with baseline mismatch ratio < 5.1, baseline mismatch ratio between 5.1 and 11.3 (OR:3.85, 95%CI 1.06-14.29, P=0.040) and mismatch ratio > 11.3 (OR:5.26, 95%CI 1.28-20.00, P=0.021) were independent protective factors of RPBE. Conclusion: In anterior circulation LVO stroke patients undergoing successful EVT, large mismatch ratio at baseline is a protective factor of rapidly progressing brain edema which is associated with poor outcomes.